2nd chance : a novel - Patterson, James, 1947-; Gross, Andrew (Boston : Little, Brown, 2002)
2nd Chance reconvenes the Women's Murder Club, four friends (a detective, a reporter, an assistant district attorney, and a medical examiner) who used their networking skills, feminine intuition, and professional wiles to solve a baffling series of murders in 1st to Die. This time, the murders of two African Americans, a little girl and an old woman, bear all the signs of a serial killer for Lindsay Boxer, newly promoted to lieutenant of San Francisco's homicide squad. But there's an odd detail she finds even more disturbing: both victims were related to city cops.
Accelerated Reader AR
Keywords: Women detectives -- California -- San Francisco -- Fiction; Women in the professions -- Fiction; Female friendship -- Fiction; San Francisco (Calif.) -- Fiction; Mystery fiction